2018
DOI: 10.1002/rcm.8166
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation pathways arising from protonation at different sites in aminoalkyl‐substituted 3‐hydroxy‐1,2,5‐oxadiazoles (3‐hydroxyfurazans)

Abstract: The product ions obtained by the competing fragmentation processes varied with the site of protonation. Interestingly, the most abundant product ions observed at low collision energies were formed by cleavage of protonated molecules possessing more internal energy than other isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In this cyclization process, a formal positive charge develops on N5 of the furazan ring and its fragmentation is analogous to the initial process characterized previously for 1a and 2a when protonated on N5. 37 The present and previous 37 computations indicated that the energy of the ion formed by protonation of the heterocyclic alkyl amine varied with protonation site, conformation, the extent of hydrogen bonding, and the tautomeric form of the heterocycle. The similar energetics provided several possibilities as starting points for fragmentation pathways and indicated that structural isomers of isobaric ions are generated during electrospray ionization.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In this cyclization process, a formal positive charge develops on N5 of the furazan ring and its fragmentation is analogous to the initial process characterized previously for 1a and 2a when protonated on N5. 37 The present and previous 37 computations indicated that the energy of the ion formed by protonation of the heterocyclic alkyl amine varied with protonation site, conformation, the extent of hydrogen bonding, and the tautomeric form of the heterocycle. The similar energetics provided several possibilities as starting points for fragmentation pathways and indicated that structural isomers of isobaric ions are generated during electrospray ionization.…”
Section: Discussionmentioning
confidence: 58%
“…Overall, the relative energies of the ions were equivalent to those computed for the shorter chain protonated ω-aminoalkyl-3-hydroxyfurazans (1a and 2a). 37 Note that protonation of the primary amino group created structural connections matching the structure of ammonia. 37 The loss of ammonia from the terminal position of an aliphatic chain has been documented for several protonated, structural analogs, such as diaminoalkanes, 42 diamino, dicarboxylic acids, 38,42 aminoalcohols, 43 muscimol, an aminomethyl substituted hydroxyisoxazole, [44][45][46] and amlodipine, an aminoethoxymethyl substituted dihydropyridine calcium channel blocker.…”
Section: Protonation Site and Initial Neutral Loss Of Ammoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Protonation of the more basic side‐chain amino group generates structural connections that closely resemble the structure of ammonia 54 . The intramolecular displacement of NH 3 by the nucleophilic α‐nitrogen, 7,8,11,28 as well as hydroxyl 29,30,42 and carboxyl 11,29 groups in bifunctional alkanes, is precedented in several previous mass spectral studies.…”
Section: Resultsmentioning
confidence: 91%